Sperm limitation affects sex allocation in a parasitoid wasp Nasonia vitripennis. (10th May 2018) - Chirault, Marlène; Bressac, Christophe; Goubault, Marlène; Lécureuil, Charlotte
Abstract: Insect reproduction is influenced by various external factors including temperature, a well‐studied constraint. We investigated to what extent different levels of sperm limitation of males exposed to different heat stresses (34 and 36 °C) affect females' offspring production and sex allocation in Nasonia vitripennis . In this haplodiploid parasitoid wasp attacking different species of pest flies, we investigated the effect of the quantity of sperm females received and stored in their spermatheca on their sperm use decisions, hence sex allocation, over successive ovipositions. In particular, we compared the sex allocation of females presenting three levels of sperm limitation (i.e., mated with control, 34 °C heat‐stressed or 36 °C heat‐stressed males) on each host they parasitized. To disentangle the potential reduction of sperm quality after a heat stress exposure from that of sperm quantity, we also explored the clutch size and sex ratio produced by females that were partially sperm limited after copulating with multiply mated males. Independently of their sperm numbers, all types of females produced a similar total number of offspring, but the more limited ones had fewer daughters. Sperm limitation further affected the distribution of daughters' production across time. In addition to constraints acting on female physiology, male fertility should therefore be considered in studies measuring reproductive outputs of insects submitted to heat stresses.